Income and food insecurity: Impact on diet quality and micronutrient intakes of females living in the United Kingdom. - Thomas, Michelle (2023)
Food insecurity in the UK is amongst the worse in Europe and was increasing before the COVID-19 pandemic and continues to increase as the UK is in the midst of a “Cost of Living Crisis”. Research has shown those at risk of food insecurity are more likely to be from low-income households, to be female, have children, have disability or are from ethnic and racial minorities. However, the monitoring of food security in the UK is in its relative infancy, it was not until 2019 that the USDA 10 question adult food security module was introduced into the Family Resource Survey, the first time all four nations of the UK food security was measured in private households.